Relationship of Handgrip Strength and Body Mass Index With Cognitive Function in Patients With Schizophrenia - Hidese, Shinsuke; Matsuo, Junko; Ishida, Ikki; Hiraishi, Moeko; Teraishi, Toshiya; Ota, Miho; Hattori, Kotaro; Kunugi, Hiroshi (Frontiers in Psychiatry, 2018)
Background: The relationship between muscle strength and cognition in schizophrenia has not been well studied. We investigated the potential relationship of handgrip strength (HGS) score and body mass index (BMI) with cognitive function in patients with schizophrenia. Methods: Participants included 153 patients with schizophrenia (age: 36.9 ± 9.4 years; 82 males) and 328 healthy controls (age: 36.4 ± 10.7 years; 150 males), matched for age, sex, and ethnicity (Japanese). HGS was measured using a digital handgrip dynamometer. Cognitive function was evaluated using the Brief Assessment of Cognition in Schizophrenia (BACS) test. A two-way multivariate analysis of covariance was used to compare HGS scores between the patient and control groups. Multiple regression analyses of BACS scores were performed in the patient and control groups using HGS and BMI scores as independent variables. Results: In the intergroup comparison, significantly lower HGS scores were observed in the patients with schizophrenia than in healthy controls (p < 0.05, corrected). In the patient group, there was a significantly positive correlation between HGS scores and BACS composite score (male, p = 0.0014; female, p = 0.0051). However, BMI scores were significantly negatively correlated with the BACS composite score (male, p = 0.0022; female, p = 0.018). Furthermore, the ratio of HGS / BMI was significantly positively correlated with BACS composite score in the patient group (p = 0.00000018). Conclusions: Cognitive function in patients with schizophrenia is correlated positively　with HGS and negatively with BMI. HGS / BMI may thus be a good index for cognitive performance in schizophrenia.